TSH-β gene polymorphism in Saudi patients with thyroid cancer: A case-control study - Maha M. AlRasheed (Elsevier, 2022)
Background: The role of thyroid-stimulating hormone in the pathogenesis of thyroid cancer is not yet fully explored. This study aimed to evaluate the role of the TSH-β polymorphism in thyroid cancer in a Saudi cohort. Methods: A prospective case-control study was conducted on 507 patients with differentiated thyroid carcinoma and compared them with 560 controls of Saudi origin. The association of two variants, the rs201857310, and rs7530810, in the TSH-β gene with thyroid cancer risk as well as thyroxine dose, were evaluated. Results: The rs201857310_A > G [OR: 0.50 (95 % CI: 0.35-0.71); P < 0.0001] was strongly associated with thyroid cancer. The multivariable analysis adjusted the effect of possible confounders (age, sex, body mass index, and smoking). Multivariable analysis elucidated that the rs201857310 maintained its significant association with the disease [OR: 0.47 (95 % CI: 0.32-0.68); P < 0.0001]. There was no significant association between the other rs7530810 variant and the disease. There was no association between any of the variants and the thyroxine dose requirement (P = 0.79 and 0.73). Conclusions: Our findings indicate that the TSH-β gene could have a role in the pathogenesis of differentiated thyroid carcinoma in the Saudi population.